An overview of lithotype associations of Miocene lignite seams exploited in Poland - Widera, Marek (Geologos, 2016)
Currently, three stratigraphically distinct lignite seams of Early to Middle Miocene age are exploited in Poland, namely the third Ścinawa lignite seam (ŚLS-3), the second Lusatian lignite seam (LLS-2) and the first Mid-Polish lignite seam (MPLS-1). All of these are composed of numerous macroscopically distinguishable layers defined as lignite lithotypes. In the present paper, the lithotypes of Polish lignites are grouped into seven major lithotype associations that originated in various types of mire. Therefore, an approximate reconstruction of mire type can be based on lignite lithotypes. Within the Polish lignite seams examined, the commonest in order of importance are: xylodetritic (XDL), detroxylitic (DXL), detritic (DL) and xylitic (XL) lithotype associations, mostly with a massive (m) or horizontal (h) structure. They are particularly dominant in lignite opencasts belonging to the Konin and Adamów mines. However, in the lowermost seams at the Turów and Bełchatów mines, a substantial part of the seams comprises the bitumen-rich (BL) lithotype association. These seams also lignite lithotypes that in large quantities have a gelified (g) and/or nodular (n) structure. In contrast, lignites from the Sieniawa mine are characterised by an admixture of the best-developed lithotype associations of both fusitic (FL) and weathered (WL) lignites. Moreover, the vast majority of these lignites have a folded (fo) and/or faulted (fa) structure, because they were completely deformed by glaciotectonics.